Modulation of Host Cell Death and Lysis Are Required for the Release of Simkania negevensis - Koch, Rebecca-Diana; Hörner, Eva-Maria; Münch, Nadine; Maier, Elke; Kozjak-Pavlovic, Vera (Frontiers in Cellular and Infection Microbiology, 2020)
Simkania negevensis is a Chlamydia-like bacterium and emerging pathogen of the respiratory tract. It is an obligate intracellular bacterium with a biphasic developmental cycle, which replicates in a wide range of host cells. The life cycle of S. negevensis has been shown to proceed for more than 12 days, but little is known about the mechanisms that mediate the cellular release of these bacteria. This study focuses on the investigation of host cell exit by S. negevensis and its connection to host cell death modulation. We show that Simkania-infected epithelial HeLa as well as macrophage-like THP-1 cells reduce in number during the course of infection. At the same time, the infectivity of the cell culture supernatant increases, starting at the day 3 for HeLa and day 4 for THP-1 cells and reaching maximum at day 5 post infection. This correlates with the ability of S. negevensis to block TNFα-, but not staurosporin-induced cell death up to 3 days post infection, after which cell death is boosted by the presence of bacteria. Mitochondrial permeabilization through Bax and Bak is not essential for host cell lysis and release of S. negevensis. The inhibition of caspases by Z-VAD-FMK, caspase 1 by Ac-YVAD-CMK, and proteases significantly reduces the number of released infectious particles. In addition, the inhibition of myosin II by blebbistatin also strongly affects Simkania release, pointing to a possible double mechanism of exit through host cell lysis and potentially extrusion.